LET'S REMEMBER OUR TEACHERS - I. V. Aksenov; O. A. Alukhanyan; S. E. Gumenyuk; A. V. Burlutckaya; V. A. Tarakanov; V. A. Porodenko; E. G. Potyagailo; G. G. Muzlaev; Е. О. Boyko; S. N. Sahnov; V. G. Nazaretyan (Кубанский научный медицинский вестник, 2017)
The article tells about the old legendary tutors of pediatric department of the Kuban state medical university. It covers the history of the development departments, which worked as a teacher, showed a huge contribution to the development of domestic and foreign medical science.